Corrosion Inhibition Potential of Indoline Dyes D149: A DFT and Monte Carlo Simulation Study - Al-Salihi, Kareem Jumaah; Kareem, Rebaz Obaid; Omer, Rebaz Anwar; Ahmed, Lana Omer; Azeez, Yousif Hussein; Hekim, Seda (Wiley, 2025)
Indoline-based dyes have emerged as highly promising materials for dye-sensitized solar cells (DSSCs) due to their straightforward synthesis, high molar absorption coefficients, and efficient photon-to-current conversion. Among them, Indoline D149 stands out for its notable optoelectronic and surface interaction properties. In this study, we comprehensively investigate the structural, electronic, and adsorption characteristics of Indoline D149 using density functional theory (DFT), time-dependent DFT (TD-DFT), and Monte Carlo simulations for the first time. The optimized geometries and electronic parameters were obtained using the B3LYP/6-311 + G(d,p) level of theory across different media (gas phase, water, DMSO, and ethanol). The results indicate that D149 possesses a high dipole moment (similar to 12.44 D in water), strong electron-donating and -accepting capabilities, and a narrow HOMO-LUMO energy gap (similar to 2.41 eV in water), signifying strong reactivity and stability. Frontier orbital analysis, molecular electrostatic potential (MEP), electron localization function (ELF), and reduced density gradient (RDG) maps highlighted active sites suitable for metal surface interaction. Fukui function analysis and quantum theory of atoms in molecules (QTAIM) further confirmed electrophilic and nucleophilic reactive centers within the molecule. Monte Carlo simulations on Fe(110) and Cu(111) surfaces in acidic environments revealed favorable adsorption configurations and significant charge transfer, indicating strong inhibition efficiency. These results support the dual role of D149 as a photoactive material and a potential eco-friendly corrosion inhibitor for industrial applications.
Keywords: corrosion inhibition; DFT; Indoline D149; Monte Carlo simulation; optoelectronic properties; surface adsorption; TD-DFT